The Searsville Lake Site (California, USA) as a candidate Global boundary Stratotype Section and Point for the Anthropocene series. (April 2023) - Stegner, M Allison; Hadly, Elizabeth A; Barnosky, Anthony D; La Selle, SeanPaul; Sherrod, Brian; Anderson, R Scott; Redondo, Sergio A; Viteri, Maria C; Weaver, Karrie L; Cundy, Andrew B; Gaca, Pawel; Rose, Neil L; et al.
Cores from Searsville Lake within Stanford University's Jasper Ridge Biological Preserve, California, USA, are examined to identify a potential GSSP for the Anthropocene: core JRBP2018-VC01B (944.5 cm-long) and tightly correlated JRBP2018-VC01A (852.5 cm-long). Spanning from 1900 CE ± 3 years to 2018 CE, a secure chronology resolved to the sub-annual level allows detailed exploration of the Holocene-Anthropocene transition. We identify the primary GSSP marker as first appearance of 239, 240 Pu (372–374 cm) in JRBP2018-VC01B and designate the GSSP depth as the distinct boundary between wet and dry season at 366 cm (6 cm above the first sample containing 239, 240 Pu) and corresponding to October-December 1948 CE. This is consistent with a lag of 1–2 years between ejection of 239, 240 Pu into the atmosphere and deposition. Auxiliary markers include: first appearance of 137 Cs in 1958; late 20th-century decreases in δ 15 N; late 20th-century elevation in SCPs, Hg, Pb, and other heavy metals; and changes in abundance and presence of ostracod, algae, rotifer and protozoan microfossils. Fossil pollen document anthropogenic landscape changes related to logging and agriculture. As part of a major university, the Searsville site has long been used for research and education, serves users locally to internationally, and is protected yet accessible for future studies and communication about the Anthropocene. Plain Word Summary: The Global boundary Stratotype Section and Point (GSSP) for the proposed Anthropocene Series/Epoch is suggested to lie in sediments accumulated over the last ~120 years in Searsville Lake, Woodside, California, USA. The site fulfills all of the ideal criteria for defining and placing a GSSP. In addition, the Searsville site is particularly appropriate to mark the onset of the Anthropocene, because it was anthropogenic activities–the damming of a watershed–that created a geologic record that now preserves the very signals that can be used to recognize the Anthropocene worldwide.